Irrigation Modernization Readiness in Environmental Quality Management Framework: Case Study of Range Irrigation, West Java - Kusumastuti, Aryati Indah; Perkasa, Windy Dwi (Tecno Scientifica Publishing, 2025)
The quality of irrigation projects in supporting sustainable development was achieved through modernization in aspects of technology, information, irrigation system management, and governance. This study aimed to develop a measurement model to evaluate irrigation modernization in supporting the quality of irrigation system management. The study was conducted in two stages. The first stage involved developing a measurement tool based on a literature review. The second stage involved testing the measurement tool to evaluate the modernization of irrigation network quality using a case study of the Rentang Irrigation Area in West Java. The evaluation was based on the preferences of staff from 14 construction service providers involved in the Rentang irrigation network improvement project. Data were analyzed using Confirmatory Factor Analysis (CFA) and multiple linear regression analysis. The results identified several important elements in the modernization of irrigation network quality, including the quality of water supply reliability, irrigation infrastructure, irrigation management systems, irrigation management institutions, and human resources. The modernization of irrigation network quality comprising improvements in water supply reliability, irrigation network reliability, irrigation management systems, irrigation management institutions, and human resources, had a positive effect on irrigation system performance. The findings provide implications for developing an irrigation modernization readiness model within a quality management framework.